Exploring the flowability, physical, and mechanical properties of eco-friendly colored cement mortars with metakaolin under sulfuric (H2SO4) and nitric acid (HNO3) attacks - Akbulut, Zehra Funda; Guler, Soner; Osmanoglu, Faruk; Kıvanç, Mehmet Rıza; Ashour, Ashraf (Journal of Building Engineering, 2024)
This article aims to investigate the flowability, physical, mechanical, and durability properties of metakaolin (MK)-added colored cement mortars exposed to the effects of H2SO4 sulfuric acid (SA) and HNO3 nitric acid (NA). MK was used in 20 % replacement with cement, and yellow (YP) and red pigments (RP) were added to the mixtures at 1 % and 3 % of the cement by weight. According to the results, although MK reduced the workability and, therefore, the flow diameter (FD) of mortars, thanks to the void-filling feature of MK, filling the voids in the microstructure caused the samples' apparent porosity (AP) and relative dynamic modulus of elasticity (RDME) to decrease. Additionally, MK significantly improved the residual compressive (RCS) and residual flexural strengths (RFS) of the samples thanks to the calcium-silicate-hydrate (C–S–H) bonds it formed in the interior structure, owing to its high pozzolanic efficiency. Moreover, this improvement of MK is more remarkable in samples that remain subject to SA and NA attacks for more time. Furthermore, while YP reduces the workability of mortars and, therefore, the FD value due to its needle-tipped grain structure, RP increases the FD value of the mortars with its spherical grain structure. However, YP and RP contributed to reducing the AP of the samples and increasing RCS and RFS capacities at a meager rate by showing a micro-filling effect. In addition, there were significant increases in the total color changes (ΔE) of YP and RP-added colored mortar samples, especially after longer SA and NA attacks. •After 56 days, SA and NA caused more harm, affecting properties.•Compared to NA, SA negatively impacted the mortar's strength and durability.•YP and RP pigments with MK enhance the mortar's resistance and durability.•Improvements in various properties offset MK's impact on workability.•Enhancing pigment ratio (1 %–3 %) improves properties in modified samples.